Coordinated loading of IRG resistance GTPases on to the Toxoplasma gondii parasitophorous vacuole - Khaminets, Aliaksandr (Blackwell Publishing Ltd, 2010)
The immunity-related GTPases (IRGs) constitute an interferon-induced intracellular resistance mechanism in mice against Toxoplasma gondii. IRG proteins accumulate on the parasitophorous vacuole membrane (PVM), leading to its disruption and to death of the parasite. How IRGs target the PVM is unknown. We show that accumulation of IRGs on the PVM begins minutes after parasite invasion and increases for about 1 h. Targeting occurs independently of several signalling pathways and the microtubule network, suggesting that IRG transport is diffusion-driven. The intensity of IRG accumulation on the PVM, however, is reduced in absence of the autophagy regulator, Atg5. In wild-type cells IRG proteins accumulate cooperatively on PVMs in a definite order reflecting a temporal hierarchy, with Irgb6 and Irgb10 apparently acting as pioneers. Loading of IRG proteins onto the vacuoles of virulent Toxoplasma strains is attenuated and the two pioneer IRGs are the most affected. The polymorphic rhoptry kinases, ROP16, ROP18 and the catalytically inactive proteins, ROP5A–D, are not individually responsible for this effect. Thus IRG proteins protect mice against avirulent strains of Toxoplasma but fail against virulent strains. The complex cooperative behaviour of IRG proteins in resisting Toxoplasma may hint at undiscovered complexity also in virulence mechanisms.